Conservative Wound Treatment in DMT2 Patients Using Honey - Laksmi, Putu Pradnyasanti; Saraswati, Made Ratna; Rooseno, Ratna Rayeni Natasha; Devinta, Made Ratih Santi; Santosa, Agus (Jurnal Ilmu Kesehatan dan Kesehatan, 2023)
Background : The number of diabetic patients in Indonesia is on the rise. In contrast to typical wounds in non DMT2 patients, chronic wounds in DMT2 patients heal more slowly, which makes it difficult to achieve complete primary wound healing. Thus, surgery is frequently required to achieve optimal healing. Patients' physical condition, age, comorbidities, and financial circumstances such as high medical costs frequently limiting patients from receiving comprehensive care, resulting alternative treatments are required to treat chronic wounds in DMT2 patients whom prefer conventional medications, addressing all circumstances. Honey, in addition to having fructose compounds, which has the benefit of increasing glucose homeostasis and insulin response, resulting in lower insulin and plasma glucose levels, also has been shown to contain anti-inflammatory and antimicrobial substances that aid in wound healing. Thus, it may be an alternative therapy for chronic wound in DMT2 patients. Methods : A Case-series studies of four DMT2 patients who were referred to Plastic and Reconstructive Outpatient ward with chronic wound were evaluated on a monthly basis following conservative treatment using Nusantara local honey-coated gauze. Result : Secondary wound healing, which can be assessed from the epithelialization process started from the peri-wound area has been obtained through monthly observations. Conclusion : Honey is used as an alternative therapy for patients with diabetic foot ulcers due to its anti-microbial and anti-inflammatory properties in the wound healing process. Furthermore, honey is considered less expensive and more affordable alternative for patients with co-morbidities that is impossible to operate, or with financial limitations. Keywords: DMT2, Chronic wound, Honey